Partial Dissociation of Truncated Peptides Influences the Structural Dynamics of the MHCI Binding Groove - Fisette, Olivier; Wingbermühle, Sebastian; Schäfer, Lars V. (Frontiers in Immunology, 2017)
Antigen processing on MHCI involves the exchange of low-affinity peptides by high-affinity, immunodominant ones. This peptide editing process is mediated by tapasin and ERAAP at the peptide C- and N-terminus, respectively. Since tapasin does not contact the peptide directly, a sensing mechanism involving conformational changes likely allows tapasin to distinguish antigen-loaded MHCI molecules from those occupied by weakly bound, non-specific peptides. To understand this mechanism at the atomic level, we performed molecular dynamics simulations of MHCI allele B*44:02 loaded with peptides truncated at the C- or N-terminus. We show that the deletion of peptide anchor residues leads to reversible, partial dissociation of the peptide from MHCI on the µs timescale. Fluctuations in the MHCI α2-1 helix segment, bordering the binding groove and cradled by tapasin in the PLC, are influenced by the peptide C-terminus occupying the nearby F-pocket. Simulations of tapasin complexed with MHCI bound to a low-affinity peptide show that tapasin widens the MHCI binding groove near the peptide C-terminus and weakens the attractive forces between MHCI and the peptide. Our simulations thus provide a detailed, spatially resolved picture of MHCI plasticity, revealing how peptide loading status can affect key structural regions contacting tapasin.